Progress in nanoscale dry processes for fabrication of high-aspect-ratio features: How can we control critical dimension uniformity at the bottom?. (25th May 2018) - Ishikawa, Kenji; Karahashi, Kazuhiro; Ishijima, Tatsuo; Cho, Sung Il; Elliott, Simon; Hausmann, Dennis; Mocuta, Dan; Wilson, Aaron; Kinoshita, Keizo
Abstract: In this review, we discuss the progress of emerging dry processes for nanoscale fabrication of high-aspect-ratio features, including emerging design technology for manufacturability. Experts in the fields of plasma processing have contributed to addressing the increasingly challenging demands of nanoscale deposition and etching technologies for high-aspect-ratio features. The discussion of our atomic-scale understanding of physicochemical reactions involving ion bombardment and neutral transport presents the major challenges shared across the plasma science and technology community. Focus is placed on advances in fabrication technology that control surface reactions on three-dimensional features, as well as state-of-the-art techniques used in semiconductor manufacturing with a brief summary of future challenges.